Um estudo de difusão de inovações tecnológicas : o caso do setor fornecedor de máquinas e equipamentos para a produção de rochas ornamentais no Espírito Santo - Silva, Maycon Chaga da (2017)
The present dissertation has as object of study the machinery and equipment sector, for ornamental rocks, in Espírito Santo, whose main purpose is to identify the form of technological diffusion observed in the sector. For this, in the analysis, the theoretical nesochumpeteriano reference is used for the description of concepts fundamental to the innovative process, among which: paradigm and technological trajectory. The neoschumpeterian approach emphasizes the importance of technological improvements as essential elements to the diffusion process, as well as the importance of the property right as motivators of this process. Technological improvements are constant and essential for the development of the machinery and equipment sector, but the existence of property rights is practically nil or inefficient. In order to fulfill the stated purpose, mainly due to the lack of research that could serve as a basis for the deepening of the knowledge about the sector, interviews with manufacturers and individuals that have been linked to the segment are used. The machinery and equipment sector grows along with the sector of ornamental rocks. Thus, it is interesting to present an overview of the sector of ornamental rocks, showing the production chain with the main links and agents involved throughout each production stage, as well as describing the world, brazilian and capixaba situation of the sector. Finally, a brief description of the formation and development of the machinery and equipment sector, highlighting CIMEF as the main driver of this segment, in Espírito Santo. An explanation, highlighting the advances of the main technologies used in the extraction and processing process, shows that the greatest technological advance occurred with the introduction of diamond wire, originally from quarries, but perfectly adapted inside sawmills, with multifibre looms. The difficulty of manufacturers in maintaining the right to own innovations, therefore, makes it possible for the main form of technological diffusion in the machinery and equipment sector to happen through imitation. A process that differs from the copy because of the imitative process allows for the occurrence of constant technological improvements, not observed with the copies, which, when not performed in the same way as the original innovation, could render the new technology unworkable.